Synthesis and Investigation of Therapeutic Potential of Isoform-Specific HDAC8 Inhibitors for the Treatment of Cutaneous T Cell Lymphoma - Umamaheswari, Appavoo; Puratchikody, Ayarivan; Hari, Natarajan (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: The available treatment option for any type of cancer including CTCL is chemotherapy and radiation therapy which indiscriminately persuade on the normal cells. One way out for selective destruction of CTCL cells without damaging normal cells is the use of histone deacetylase inhibitors (HDACi). Despite promising results in the treatment of CTCL, these HDACi have shown a broadband inhibition profile, moderately selective for one HDAC class but not for a particular isotype. The prevalence of drug-induced side effects leaves open a narrow window of speculation that the decreased therapeutic efficacy and observed side effects may be most likely due to non specific HDAC isoform inhibition. The aim of this paper is to synthesis and evaluates HDAC8 isoform specific inhibitors. Methods: Based on the preliminary report on the design and in silico studies of 52 hydroxamic acid derivatives bearing multi-substituent heteroaromatic rings with chiral amine linker, five compounds were shortlisted and synthesized by microwave assisted approach and high yielding synthetic protocol. A series of in vitro assays in addition to HDAC8 inhibitory activity was used to evaluate the synthesised compounds. Results: Inhibitors 1e, 2e, 3e, 4e and 5e exerted the anti-proliferative activities against CTCL cell lines at 20- 100 μM concentrations. Both the pyrimidine- and pyridine-based probes exhibited μM inhibitory activity against HDAC8. The pyrimidine-based probe 1e displayed remarkable HDAC8 selectivity superior to that of the standard drug, SAHA with an IC50 at 0.1μM. Conclusion: Our study demonstrated that simple modifications at different portions of pharmacophore in the hydroxamic acid analogues are effective for improving both HDAC8 inhibitory activity and isoform selectivity. Potent and highly isoform-selective HDAC8 inhibitors were identified. These findings would be expedient for further development of HDAC8-selective inhibitors.
Keywords: hydroxamates